Identification of early quassinoid biosynthesis in the invasive tree of heaven (Ailanthus altissima) confirms evolutionary origin from protolimonoids - Chuang, Ling; Liu, Shenyu; Biedermann, Dave; Franke, Jakob (Frontiers in Plant Science, 2022)
The tree of heaven, Ailanthus altissima (MILL.) SWINGLE, is a globally invasive plant that is known to secrete allelopathic metabolites called quassinoids. Quassinoids are highly modified triterpenoids. So far, nothing has been known about the biochemical basis of quassinoid biosynthesis. Here, based on transcriptome and metabolome data of Ailanthus altissima, we present the first three steps of quassinoid biosynthesis, which are catalysed by an oxidosqualene cyclase and two cytochrome P450 monooxygenases, resulting in formation of the protolimonoid melianol. Strikingly, these steps are identical to the first steps of the biosynthesis of limonoids, structurally different triterpenoids from sister plant families within the same order Sapindales. Our results are therefore not only important to fully understand the biosynthesis of complex triterpenoids in plants, but also confirm the long-standing hypothesis that quassinoids and limonoids share an evolutionary origin. In addition, our transcriptome data for Ailanthus altissima will be beneficial to other researchers investigating the physiology and ecology of this invasive tree.